ASEAN matters reflecting on the Association of Southeast Asian Nations - Lee, Yoong Yoong (World Scientific Publishing Co., Pte, Ltd., 2011)
The initiative to establish the Association of Southeast Asian Nations (ASEAN) Community was adopted by the ten leaders at the 2003 Bali Summit in Indonesia. Since then, the concept of a community-building process in ASEAN has become an issue that attracts a great deal of attention from scholars and experts around the world. ASEAN Matters! Reflecting on the Association of Southeast Asian Nations carries essays with different perspectives on critical issues relating to the three pillars in building the ASEAN Community, namely the ASEAN Political and Security Community; the ASEAN Economic Community; and the ASEAN Socio-Cultural Community. In a nutshell, this book provides broad and invaluable insights into the role ASEAN plays in enhancing peace, prosperity, and stability in the Southeast Asian region.